2014
DOI: 10.1155/2014/472516
|View full text |Cite
|
Sign up to set email alerts
|

Boost IORT in Breast Cancer: Body of Evidence

Abstract: The term IORT (intraoperative radiotherapy) is currently used for various techniques that show decisive differences in dose delivery. The largest evidence for boost IORT preceding whole breast irradiation (WBI) originates from intraoperative electron treatments with single doses around 10 Gy, providing outstandingly low local recurrence rates in any risk constellation also at long term analyses. Compared to other boost methods, an intraoperative treatment has evident advantages as follows. Precision. Direct vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…Even though data from the TARGIT-A and ELIOT trial suggest that IORT may be an oncological reliable alternative to conventional postoperative fractionated irradiation in a low to medium risk collective [12], IORT is routinely used only as a boost followed by whole breast radiation in our hospital. IORT can be considered a safe treatment modality [13][14][15][16][17][18] but only a few authors have published data on IORT and seroma production [19].…”
Section: Discussionmentioning
confidence: 99%
“…Even though data from the TARGIT-A and ELIOT trial suggest that IORT may be an oncological reliable alternative to conventional postoperative fractionated irradiation in a low to medium risk collective [12], IORT is routinely used only as a boost followed by whole breast radiation in our hospital. IORT can be considered a safe treatment modality [13][14][15][16][17][18] but only a few authors have published data on IORT and seroma production [19].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the risk of fat necrosis after APBI increases with lower dose homogeneity and higher volumes of tissue exposes to 150 and 200% of the prescription dose [39,40]. Although cosmesis would theoretically be improved with IORT because there is less irradiation of normal tissue [41,42], there is also the potential for worse cosmesis because of a lack of symmetry within the irradiated breast [43]. Careful patient selection, future science group www.futuremedicine.com considering tumor-to-breast ratio and distance to skin is critical.…”
Section: • • High Single-fraction Dosementioning
confidence: 99%
“…An alternative to standard EBRT is intraoperative radiation therapy (IORT) in which at the time of breast conserving surgery a single dose of radiation is delivered 3. Unlike other types of radiotherapy, intraoperative radiotherapy (IORT) delivers a high single dose of radiation to the area around the tumor bed.…”
Section: Introductionmentioning
confidence: 99%
“…This shorter treatment option has been hypothesized to improve patient compliance, cost, and overall experience 9. Since the 20 Gy dose of IB‐IORT is biologically much greater than the fractional doses of EBRT, initially there was concern for an increase in toxicity, but studies have shown no treatment related mortality or excess morbidity including problems with wound healing, infection, or cosmetics 3, 9. One major difference between IB‐IORT and EBRT is breast changes such as fat necrosis and other distinct mammographic changes, which can complicate future diagnostic mammography, although usually, these changes are easily discernible from recurrent tumors 9.…”
Section: Introductionmentioning
confidence: 99%